Penerapan e-literasi dalam menanggapi infodemik COVID-19 di media sosial - Hikmah Irfaniah; Ade Abdul Hak; Fahma Rianti (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. The spread of the infodemic during the COVID-19 pandemic prompted the need for e-literacy to counteract the negative impacts it had. This study aims to describe how students apply e-literacy in response of infodemic on social media. Data Collection Methods. This research is a qualitative research using a phenomenological approachthrough interviews. The four informants of this study are students of Library Science at UIN Syarif Hidayatullah Jakarta. Data Analysis. Data analysis was conducted by reducing the results of the interviews, coding, then connecting themes and descriptions, and interpreting them. Results and Discussion. In communicating infodemic, students apply e-literacy by operating laptops and mobile phones in accessing information; find, evaluate, and use information according to their needs; consider ethics, religion, and social norms in communication; access, analyze, evaluate, and create infodemic content on social media; as well as being able to absorb information, transform and create new ideas. Conclusion. Library Science students are able to apply e-literacy in communication on social media, both in consuming and producing information related to COVID-19. Research on e-literacy aside from the infodemic and post-pandemic needs to be carried out to see the results of e-literacy implementation.